Phylogeographic analysis of the chloroplast DNA variation in wild common bean (Phaseolus vulgaris L.) in the Americas - Chacón Sánchez, María I.; Pickersgill, B; Debouck, Daniel G.; Arias, J.S. (Springer, 2007)
The wild common bean (Phaseolus vulgaris) is widely but discontinuously distributed from northern Mexico to northern Argentina on both sides of the Isthmus of Panama. Little is known on how the species has reached its current disjunct distribution. In this research, chloroplast DNA polymorphisms in seven non-coding regions were used to study the history of migration of wild P. vulgaris between Mesoamerica and South America. A penalized likelihood analysis was applied to previously published Leguminosae ITS data to estimate divergence times between P. vulgaris and its sister taxa from Mesoamerica, and divergence times of populations within P. vulgaris. Fourteen chloroplast haplotypes were identified by PCR-RFLP and their geographical associations were studied by means of a Nested Clade Analysis and Mantel Tests. The results suggest that the haplotypes are not randomly distributed but occupy discrete parts of the geographic range of the species. The current distribution of haplotypes may be explained by isolation by distance and by at least two migration events between Mesoamerica and South America: one from Mesoamerica to South America and another one from northern South America to Mesoamerica. Age estimates place the divergence of P. vulgaris from its sister taxa from Mesoamerica at or before 1.3 Ma, and divergence of populations from Ecuador-northern Peru at or before 0.6 Ma. As these ages are taken as minimum divergence times, the influence of past events, such as the closure of the Isthmus of Panama and the final uplift of the Andes, on the migration history and population structure of this species cannot be disregarded.